Ultra-low jitter mode-locked fiber laser - Wu, Kan (2012)
Lasers have been widely used in various fields since the invention of first laser in 1960. Low-noise passively mode-locked lasers, as a special kind of pulsed lasers, provide ultra low intensity fluctutation and timing jitter and therefore have significant applications in optical sampling, frequency metrology and high-precision clock distribution, etc. Therefore, it is important to investiage the methods to reduce the phase noise and timing jitter of the mode-locked lasers. Moreover, various noise conversion phenomena also affect the laser noise such as the noise conversion from the pump to the mode-locked lasers, or degrade the microwave signal quality synthesised from the mode-locked lasers such as the excess phase noise conversion in the photodetectors. It is also meaningful to understand and characterize these noise conversion phenomena.